SYNTHESIS OF 1,2,3-TRIAZOLES BASED ON PHENACYL AZIDE DERIVATIVES VIA CLICK CHEMISTRY - Jwad, Rasha; Mohammed, Adnan; Shihab, Mehdi (Iraqi Journal of Science, 2024)
Etherification of n-hexanol, n-heptanol and n-octanol with propargyl bromide in the presence of sodium hydroxide in DMF afforded the terminal alkynes (2) a, b and c. Phenacyl bromide, p-bromophenacyl bromide and p-phenylphenacyl bromide were converted to corresponding azides (4) a, b and c respectively by traditional SN2 reaction of the mentioned bromides and sodium azide in DMF. The cycloaddition of the propargyl ethers (2) with the prepared organic azides (4) using click conditions gave the target 1,4-disubstituted 1,2,3- triazoles (5)-(7) in good yields. All the synthesized triazoles were characterized by FT-IR while the compounds (5) a,b and c were characterized by 1H NMR and 13C NMR in addition to FT-IR technique.